Survey and distribution of rodent inhabiting eight districts at Gharbia governorate, Egypt - Al-Gendy, A. T.R.; Al-Akraa, T. M.M.; Abd-El-Hamed, Wafaa F.; El-Shazly, Safaa A. (Journal of Phytopathology and Disease Management, 2017)
Rodent individuals were noticed in buildings from eight districts viz., Samannoud, El-Mahala, Tanta, Elsanta, Zifta, Bassuon, Kotor and Kafr-El-Zayat districts during two years at Gharbia Governorate, Egypt. The residents noticed 193, 146, 112, 109, 102, 82, 77 and 34 rodent individuals in Samannoud, El-Mahala, Tanta, Elsanta, Zifta, Bassuon, Kotor and Kafr-El-Zayat districts respectively during from January 2014 to December 2016 at Gharbia Governorate. There was no significant difference between number of rodent during study period (years), but there was significant difference among places and months. Rodents recorded in Elsanta and Tanta distracts were Rattus rattus (Linn.), Rattus rattus frugivorous (Rafinesque) and Rattus rattus alexandrines (Geoffray) and Rattus norvegicus Berk., and Mus musculus Linn., belonging to two genera (Rattus and Mus) from family Muridae. There was no significant difference between number of rodent during (cities, years and species) but there was significant difference between number of rodent during months and locations. These results could be used in the Integrated Pest Management program to control the rodents. This work proved the presence of R. rattus (Linn.);(R.rattus frugivorous (Rafinesque) and R. rattus alexandrines (Geoffray)] followed by R. norvegicus Berk., and Mus musculus Linn., belonging to two genera (Rattus and Mus) from family Muridae, were recorded in Elsanta and Tanta distracts at Gharbia Governorate. R. norvegicus Berk.; R. rattus frugivorous (Rafinesque) followed by. R. rattus alexandrines (Geoffray); were recorded in Elsanta and Tanta districts. The highest number of R. norvegicus Berk., were recorded 6 individuals during Summer and Winter seasons in 1st year while 8 individuals were recorded during Autumn in 2nd year from AL-Santa district. The highest number of R. norvegicus Berk., (8 individuals) were recorded during Spring season in 1st year while 5 individuals were recorded during Winter and Spring seasons in 2nd year from Tanta distract. The highest number of R.rattus frogivorus (Rafinesque) were recorded 5 individuals during Spring season in1st year while 6 individuals were recorded during Winter season in 2nd year from Al-Santa district. The highest number of R. rattus frogivorus (Rafinesque),(4 individuals) were recorded during Summer seasonin1st year while 4 individuals were recorded during Summer, Autumm and Winter seasons in 2nd year from Tanta district. The highest numbers of R. rattus alexandrines (Geoffray) were recorded 5 individuals during Spring season in1st year while 6 individuals were recorded during Spring in 2ndyear from Al-Santa district. The highest number of R. rattus alexandrines (Geoffray).,(4 individuals) were recorded during Summer season in 1st year while 4 individuals were recorded during Summer, Autumm and Winter seasons in 2nd year from Tanta district. There were no significant difference between number of rodent during (Cities, Years and Species) but there were significant difference between number of rodent during months and locations.